Записки революционера: мемуары / П. А. Кропоткин - Кропоткин Петр Алексеевич (Мысль, 1990)
Экземпляры: ф.20 (1990) / Инвентарный номер: 32140 / Цена: / Сис.шифр: 63.3(2)5 / Авт.знак: К 83 / ГРНТИ: 03.23.31 / ББК: 63.3(2)5